Analysis of Formation of Register Language Word on Selling and Purchase of Phones on Social Media Instagram @pst0re - Fitri Asih, Ferdianti; Lukmanul Hakiem, Fakhry; Suta Wardianto, Bayu (International Proceedings of Nusantara Raya, 2023)
This study aims to describe the process of word formation and the function of register language in seller captions and discussions that occur in the comments column on Pst0re's Instagram social media. This research uses descriptive qualitative method. The data collection technique in this research is using the technique of simak libat cakap and the technique of free simak libat cakap. The validity of the research is carried out using investigative techniques by comparing individual opinions with parties who have expertise in accordance with their fields. Data analysis uses the commensurate method technique. This is a method with determining tools related to parts outside the language and with determining tools of the language elements themselves. The result of this research, there are 3 word formation processes (1) affixation (2) reduplication and (3) abbreviation. Then there are 4 functions of register language, including (a) instrumental function, (b) representational function, (c) heuristic function, and (d) interactional function.